The Marriage Prohibitions - Rachmat Husein Rambe; Faisar Ananda; Irwansyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Marriage in Islam is a noble act of worship and a means to create a life filled with love, tranquility, and blessings within the family. Islam sets clear rules regarding who is permitted and prohibited from marrying, with the aim of preserving the sanctity and harmony of family relationships as well as the welfare of the community. In the Qur'an, there are two types of marriage prohibitions: permanent (mu'abbad) and temporary prohibitions. The permanent prohibitions include marriage with close relatives such as siblings, mothers, stepmothers, and married women, while temporary prohibitions apply in certain conditions, such as women in the waiting period (iddah) or those who are menstruating or postpartum. Additionally, there are other prohibitions, such as marrying someone of a different faith (except for a Muslim man marrying a woman from the People of the Book) or marrying more than four women without the ability to treat them justly. These prohibitions aim to protect the well-being of individuals and families, ensuring that marriages create a home that is peaceful, loving, and blessed by Allah.